The application of chromatography techniques for the purification process optimization of amide of hydrocortisone-derived cortienic acid and ethyl ester of L-glycine - Dobričić Vladimir; Vladimirov Sote; Čudina Olivera (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Soft ('antedrug') glucocorticoids are pharmacologically active compounds which are biotransformed in a predictable and controllable way to inactive and non-toxic metabolites. Amides of cortienic acids (17(-carboxamide derivatives of glucocorticoids) are potential soft drugs with fewer side effects than traditional glucocorticoids. The purification of 17(- carboxamide derivatives of hydrocortisone was explained using the amide of hydrocortisonederived cortienic acid and ethyl ester of L-glycine as an example and performed by use of column chromatography and preparative thin-layer chromatography (TLC). The optimization of purification process was performed employing analytical TLC and reversed-phase highperformance liquid chromatography (RP-HPLC). The mobile phase that enables best chromatographic separation of the amide from impurities on TLC plate (chloroform-methanol (95:5 V/V)) was selected and modified (reduction of polarity and addition of glacial acetic acid) to be used for the column chromatography and preparative TLC purification. It was confirmed by use of RP-HPLC that purification procedures applied in this study resulted in pure (96.2 %) amide.